Cervical cancer screening coverage and associated factors among women aged 25–59 in Eswatini: Insights from the 2021 Population-Based HIV Impact Assessment (PHIA) - Abenezer Melaku Tafese; Bikiltu Dirbaba; Meseker Fentie; Charnita Zeigler-Johnson (PLoS ONE, 2026)
Background Cervical cancer is the most common cancer and the leading cause of cancer mortality among women in Eswatini, which reported the highest cervical cancer incidence and mortality rates globally in 2022. However, recent nationally representative published data on cervical cancer screening coverage in Eswatini remain limited. This study aimed to estimate cervical cancer screening coverage and identify factors associated with screening uptake among women aged 25–59 years in Eswatini. Method Data were drawn from the 2021 Eswatini Population-based HIV Impact Assessment (PHIA), a nationally representative cross-sectional household survey. Survey-weighted bivariable and multivariable logistic regression analyses were conducted to identify factors associated with screening uptake. Results are reported as adjusted odds ratios (AORs) with 95% confidence intervals (CIs). Result Among 3,192 women aged 25–59 years, 48.2% reported ever having undergone cervical cancer screening. Higher odds of screening were observed among women living with HIV (AOR 2.26, 95% CI 1.93–2.65), those aged 36–45 years (AOR 1.35, 95% CI 1.12–1.62), and those in the fourth wealth quintile (AOR 1.40, 95% CI 1.05–1.88). Lower odds of screening were observed among women who were not married (AOR 0.65, 95% CI 0.54–0.78), with no formal education (AOR 0.56, 95% CI 0.39–0.80), no recent healthcare visit (AOR 0.67, 95% CI 0.55–0.83), no family planning use (AOR 0.82, 95% CI 0.69–0.97), and one sexual partners (AOR 0.78, 95% CI 0.65–0.94). Conclusion Despite notable progress, cervical cancer screening coverage in Eswatini remains below World Health Organization targets. Enhancing community awareness, addressing stigma and structural barriers, and integrating cervical cancer screening into routine and reproductive healthcare services may accelerate progress toward achieving the WHO 2030 targets.